2008
DOI: 10.1063/1.2966693
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Raman of O–H/O–D vibrations and photoluminescence studies in LiTaO3 thin film

Abstract: Resonant Raman spectra (RRS) of O-H and O-D vibration and libration modes, their combinations and higher harmonics have been observed in LiTaO 3 polycrystalline thin films. RRS peaks are superimposed on photoluminescence (PL) spectrum. Monochromatic light from a xenon lamp is used as excitation source. PL spectrum shows two broad peaks, first near the band gap in UV (4.4-4.8eV) and another in the sub band gap region (< 4.0 eV). Band gap PL along with RRS peaks are reported for the first time. Photoluminescence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…We acquired the Raman scattering spectra of LTO and S-LTO powders by stimulating the samples with a laser source of 514 nm (Figure d). The Raman spectrum of the LTO sample comprises peaks at 854, 659, 590, 457, 378, 347, 305, 251, and 204 cm –1 that match with the optical phonon modes that have been reported for congruent LiTaO 3 . The peaks below 432 cm –1 belong to Li–O stretching and O–Li–O bending modes, and peaks at 550–850 cm –1 range can be attributed to Ta–O stretching modes . The Raman spectrum of the S-LTO sample shows only a broad peak at 640 cm –1 but does not have all of the other peaks observed in the Raman spectrum of the LTO sample.…”
Section: Resultssupporting
confidence: 69%
“…We acquired the Raman scattering spectra of LTO and S-LTO powders by stimulating the samples with a laser source of 514 nm (Figure d). The Raman spectrum of the LTO sample comprises peaks at 854, 659, 590, 457, 378, 347, 305, 251, and 204 cm –1 that match with the optical phonon modes that have been reported for congruent LiTaO 3 . The peaks below 432 cm –1 belong to Li–O stretching and O–Li–O bending modes, and peaks at 550–850 cm –1 range can be attributed to Ta–O stretching modes . The Raman spectrum of the S-LTO sample shows only a broad peak at 640 cm –1 but does not have all of the other peaks observed in the Raman spectrum of the LTO sample.…”
Section: Resultssupporting
confidence: 69%
“…In TRR, the following processes (a) electronic excitation and recombination, (b) electronlattice phonon transition and (c) electron-defect vibrational transition are in resonance. Initial studies of PL of LiTaO 3 thin films have also shown dispersion of the OH stretching mode of the same magnitude [18]. The aim of this paper is to show that the large dispersion of RR peaks seems to be a common property of oxides with impurities of CO and OH.…”
Section: Introductionmentioning
confidence: 77%